IMPLEMENTASI PENERAPAN APLIKASI SAMBARA DALAM ADMINISTRASI WAJIB PAJAK PADA MASA PANDEMI COVID-19 DI KABUPATEN KARAWANG - Sri Fitria Mulyadi; Dadan Kurniansyah; Made Panji Teguh Santoso (Institut Pemerintahan Dalam Negeri, 2021)
This study will explain the implementation of the Sambara application in the administration of taxpayers during the Covid-19 pandemic at Samsat, Karawang Regency, Sambara is an electronic-based innovation made by the West Java Regional Revenue Agency whose function is to check motor vehicle tax payments online on the application. Sambara in West Java, the application can display motor vehicle tax information both two-wheeled and four-wheeled and can make tax payments through Alfamart Indomart outlets, and in this application, a feature can find out the schedule for mobile Samsat, as well as find out the location of the nearest Samsat service in all regions. in West java. This study analyzes it using the theory of Charles O. Jones (1996). And this research uses descriptive qualitative methods with a literature review with a qualitative approach, research results from the organization, application, and interpretation of the Karawang Regency Samsat have implemented the Sambara application since 2018 until now quite a lot of people have used the Sambara application in the tax payment process. motorized vehicles and this application can be well received by the public